FIFA Women`s World Cup 2019-2023: a PCA approach to the evolution of technical event performance data and key performance indicators - Lopes, R.; Yousefian, F.; Gómez-Ruano, M. Á.; Galvão, M.; Brito, J.; Travassos, B. (International Journal of Performance Analysis in Sport, 2025)
This study aimed to investigate the evolution of technical event performance data during the 2019 and 2023 FIFA Women`s World Cup tournaments, seeking to identify key performance indicators crucial to national team`s success. Data across the tournaments were analysed using principal component analysis. Results revealed four principal components. Subsequently, linear mixed model analyses were performed to assess differences between (a) team success (win, loss, or draw), (b) group positions (1st, 2nd, 3rd and 4th) and (c) phases of the tournament (group, round of 16, quarter-final, semi-final and final). The findings indicate no significant differences in KPIs between the two tournaments (p > 0.05). However, the third principal component, representing effectiveness in the attacking phase, showed significant differences (p < 0.05) for general classification (ES = 0.0910), group classification (ES = 0.0693) and match results (ES = 0.0798), highlighting the importance of goal-scoring efficiency. The second component, representing attacking involvement, showed significant differences (p < 0.05) for both group classification (ES = 0.0982) and match results (ES = 0.109), reinforcing the critical role of offensive actions in match outcomes. The findings can help national teams improve their preparation for international competitions by focusing on key technical, tactical and physical performance dimensions.